The transformation of finance in Europe: introduction and overview - Eric Perée; Armin Riess (EIB Papers, 2003)
This paper introduces the topic of Europe's changing financial landscape and highlights the findings of the contributions to this volume of the EIB Papers. Key points emerging from this overview include: (i) a variety of factors are reshaping Europe's finance, notably the Single Market, EMU, demographic trends, increasing wealth, technological progress, and financial innovation; (ii) further integrating Europe's financial systems, across borders and segments, should significantly increase economic welfare; (iii) although the functions that financial systems perform are being reallocated - implying a move towards the Anglo-Saxon paradigm - banks will remain important and should maintain their comparative advantage in financing small and medium-sized enterprises; (iv) the economic case in favour of a move towards funded pension systems - which would boost capital markets - is not as compelling as often assumed.
Keywords: 330; Finanzsektor; Finanzmarkt; Wohlfahrtseffekt; Branchenentwicklung; EU-Staaten